Application of Box-Behnken Design to the Study of Fatty Acids and Antioxidant Activity from Enriched White Bread - Maruyama, Swami A.; Palombini, Sylvio V.; Claus, Thiago; Carbonera, Fabiana; Montanher, Paula F.; Souza, Nilson E. de; Visentainer, Jesuí V.; Gomes, Sandra T. M.; Matsushita, Makoto (Journal of the Brazilian Chemical Society, 2013)
This work determined the proximate/fatty acid composition and the antioxidant activity of breads using a Box-Behnken design composed of fifteen experiments and three factors. The studied breads had altered baking times and the wheat flour was partially substituted by chia seeds and carrot leaves. Total antioxidant capacity results were superior to those obtained from control bread (495.33 µmol TEAC g-1 for DPPH assays and 413.85 µmol TEAC g-1 for FRAP assays), showing increased levels of 97 and 102% for DPPH and FRAP assays, respectively. The addition of chia seeds and carrot leaves led to maximal alpha-linolenic acid increase of 216.69% and maximum PUFA:SFA ratio increase of 18.88% in relation to control bread (this with alpha-linolenic acid amount of 34.03 mg g-1 total lipid and a 2.86 ratio value), as well as a maximum omega-3:omega-6 ratio reduction of 70.01% (15.59 ratio value for control bread).